ʻAnusō̜n nai ngān phrarātchathān phlœ̄ng sop Mō̜m Dutsadī Bō̜riphat Na ʻAyutthayā Thō̜.C̜hō̜., Bō̜.Chō̜., na mēn lūang nā phlapphlā ʻItsariyāphō̜n Wat Thēpsirinthrāwāt, Wanʻāthit thī 19 Mithunāyon Phutthasakkarāt 2559 - Dutsadī Bō̜riphat Na ʻAyutthayā ([Verlag nicht ermittelbar], 2016)
Cremation volume for Dutsadi Boriphat Na Ayutthaya, Mom,1924-2015, a former Thai teacher, writer and translator,etc.; comprises biography, condolences and articles on Thai cooking, and Thai poems translated into English by the crematee, หม่อม ดุษฎี บริพัตร ณ อยุธยา, Nangsư̄ ‘Anusō̜n ngānsop
Keywords: Autobiografie; Biografie; Festschrift; Kochbuch; Educators; Teachers; Authors; Thai; Cooking; Thai; Cremation Volume